Choledochal Cyst with 17q12 Chromosomal Duplication. (22nd September 2017) - Kotalova, Radana; Dusatkova, Petra; Drabova, Jana; Elblova, Lenka; Dedic, Tomas; Cinek, Ondrej; Lebl, Jan; Pruhova, Stepanka
Summary: The 17q12 chromosomal region carries the HNF1B gene, mutations of which cause various conditions. When searching for HNF1B/ 17q12 rearrangements among children with biliary atresia and/or choledochal cysts, we identified a male proband carrying a 17q12 duplication spanning 1698 kb that included 24 genes from TBC1D3C to HNF1B . The boy presented with cholestatic jaundice at the age of 2 weeks due to a choledochal cyst sized 15 ×12 mm (type Ia according to the Todani classification). He underwent a shunt surgery consisting of a hepaticojejunostomy using Roux‐en‐Y loop at the age of 2 months, which led to a permanent relief of cholestasis. Perioperative liver histology revealed significant hepatic fibrosis and bile ductular proliferation. At 17 years, he has a mildly enlarged liver with decreased elasticity, an upper‐normal–sized spleen, normal biochemistry values, and no renal or hepatic cysts. We report the first hepatobiliary phenotype in a patient with an HNF1B overdosage.